Profound loss of general knowledge in retrograde amnesia: evidence from an amnesic artist - Gregory, Emma; McCloskey, Michael; Landau, Barbara (Frontiers in Human Neuroscience, 2014)
Studies of retrograde amnesia have focused on autobiographical memory, with fewer studies examining how non-autobiographical memory is affected. Those that have done so have focused primarily on memory for famous people and public events—relatively limited aspects of memory that are tied to learning during specific times of life and do not deeply tap into the rich and extensive knowledge structures that are developed over a lifetime. To assess whether retrograde amnesia can also cause impairments to other forms of general world knowledge, we explored losses across a broad range of knowledge domains in a newly-identified amnesic. LSJ is a professional artist, amateur musician and history buff with extensive bilateral medial temporal and left anterior temporal damage. We examined LSJ's knowledge across a range of everyday domains (e.g., sports) and domains for which she had premorbid expertise (e.g., famous paintings). Across all domains tested, LSJ showed losses of knowledge at a level of breadth and depth never before documented in retrograde amnesia. These results show that retrograde amnesia can involve broad and deep deficits across a range of general world knowledge domains. Thus, losses that have already been well-documented (famous people and public events) may severely underestimate the nature of human knowledge impairment that can occur in retrograde amnesia.